Hedwig and the angry inch - Mitchell, John Cameron (Warner Brothers, 2001)
A gender-queer punk-rock singer from East Berlin tours the U.S. with her band as she tells her life story and follows the former lover/band-mate who stole her songs.
Keywords: allemagne; amériques; approches et analyses; cinéma; communication; cours; discipline; europe; fem3200; genre; identités LGBTQIA2+; premier cycle; queer; régions géographiques; thématiques; états-unis